A card agglutination test for dog erythrocyte antigen 1 (DEA 1) blood typing in donor dogs: Determining an appropriate cutoff to detect positivity using a receiver operating characteristic curve. (24th October 2019) - Proverbio, Daniela; Perego, Roberta; Baggiani, Luciana; Spada, Eva
Abstract: Background: The appropriate cutoff to define a positive point‐of‐care card agglutination (CA) test for dog erythrocyte antigen 1 (DEA 1) blood typing depends on whether the test can be used in the donor or recipient. Objectives: By screening for CA test positivity, we aimed to evaluate the best cutoff value for DEA 1 blood typing in canine blood donors using a receiver operator characteristic (ROC) curve. Methods: Ethylenediaminetetraacetic acid (EDTA) blood samples from 100 canine blood donors were blood‐typed in parallel for DEA 1 using both immunochromatographic (IC) and CA tests. The effect of temperature, storage time, and anticoagulant solutions for both methods was evaluated. Unweighted and weighted Cohen's Kappa ( K ) statistic was calculated to evaluate the agreement between the two testing methods. The overall performance of the CA test was evaluated by generating a ROC curve using the IC test as the reference method. Results: Concordant results were obtained for 86% of the samples. Unweighted and weighted K statistics demonstrated good and moderate agreement, respectively. For the CA test, the ROC curve showed an area under the curve (AUC) of 0.910, with the highest sensitivity cutoff values at ≥1+ agglutination. CA‐ and IC‐typed EDTA blood samples stored at room temperature for up to 1 week and refrigerated for up to 1 month were concordant as were the citrate phosphate dextrose adenine 1 (CPDA‐1) anticoagulated blood samples stored for up to 1 week at 4 ± 2°C. Conclusions: The overall reliability of the CA method seemed to be lower than that of the IC method. When CA is used as a screening test for canine blood donors, the correct cut off is ≥1+ agglutination is recommended to maximize sensitivity.